1969
DOI: 10.1002/cpt1969103401
|View full text |Cite
|
Sign up to set email alerts
|

The metabolism of amiloride hydrochloride in man

Abstract: Amiloride hydrochloride labeled with C14 was given to 5 volunteers. Serum level peaked at 3 hours, and the half‐life was 6 hours. There was no evidence of metabolic transformation of amiloride. Approximately half the oral dose was recovered in the urine. Amiloride is cleared by tubular transport and should be used with caution in patients with renal insufficiency.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
27
0

Year Published

1980
1980
2008
2008

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 74 publications
(32 citation statements)
references
References 3 publications
5
27
0
Order By: Relevance
“…This finding is not surprising in view of the highly charged nature of the molecule and the fact that previous studies by Weiss et al (1969) have shown it to be excreted unchanged in the urine. Although previous reports of hyperkalaemia associated with the use of amiloride have concerned patients receiving 15 or 20 mg daily, it would appear from the present data that its use in smaller doses is potentially hazardous in those who are severely ill or who have renal failure.…”
Section: Amiloride Handling In Renal Failuresupporting
confidence: 64%
See 2 more Smart Citations
“…This finding is not surprising in view of the highly charged nature of the molecule and the fact that previous studies by Weiss et al (1969) have shown it to be excreted unchanged in the urine. Although previous reports of hyperkalaemia associated with the use of amiloride have concerned patients receiving 15 or 20 mg daily, it would appear from the present data that its use in smaller doses is potentially hazardous in those who are severely ill or who have renal failure.…”
Section: Amiloride Handling In Renal Failuresupporting
confidence: 64%
“…All gave informed consent to entering the study which had been approved by the local ethical committee. After fasting, each patient took a Weiss et al (1969) Blood samples (10 ml) were drawn at time zero and at 1, 2, 3, 4, 6, 8 and 24 h after dosing and thereafter at appropriate time intervals up to 9 days. Urine was collected for 72 h in 4 patients and for 7 days in the fifth.…”
Section: Amiloride Handling In Renal Failurementioning
confidence: 99%
See 1 more Smart Citation
“…The In humans, approximately 50% of an oral dose of amiloride is recovered in urine as unchanged amiloride (Weiss et al, 1969). The remainder of the dose probably represents either unabsorbed drug or biliary and or intestinal clearance, as several investigators have recovered up to 50% of the dose in faeces after oral dosing (Weiss et al, 1969;George, 1980;unpublished observations It is apparent that renal function is the major factor influencing the disposition of amiloride. There was a highly significant, strong, negative correlation between age and creatinine clearance, a relationship which has been previously decribed (Lindeman et al, 1985).…”
Section: Pharmacokinetic and Statistical Analysesmentioning
confidence: 99%
“…The potassium sparing diuretics amiloride and studied (Smith & Smith, 1973;Weiss et al., triamterene still play an important role in attenu-1969). One reason for the paucity of documentaating the potassium-wasting effects of thiazide tiQn has been the lack of a sufficiently sensitive and more potent loop diuretics.…”
Section: Introductionmentioning
confidence: 99%